2020
DOI: 10.4314/ejhs.v30i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Medication Adherence among Hypertensive Patients in Deprived Rural Areas

Abstract: BACKGROUND: Poor adherence to medication regimen leads to poor health outcomes, increased medical costs and increased death rate due to hypertension. The aim of this study was to evaluate baseline barriers to medication adherence among hypertensive patients in deprived rural areas.METHODS: A cross-sectional study was conducted on 238 hypertensive patients living in deprived rural areas of Iran. Data were collected using a questionnaire consisting of demographic information, Morisky medication adherence scale a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…The heterogeneity obtained in this study was quite high; this could be due to differences in the population of the research subjects. The largest number of samples is in the [18], as many as 1208, and the smallest number of samples as many as 117. The results of data analysis from this study showed that there was no relationship between gender and adherence to medication for hypertension patients.…”
Section: B Meta-analysis Of the Relationship Between Gender And Medication Adherence Of Hypertensive Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterogeneity obtained in this study was quite high; this could be due to differences in the population of the research subjects. The largest number of samples is in the [18], as many as 1208, and the smallest number of samples as many as 117. The results of data analysis from this study showed that there was no relationship between gender and adherence to medication for hypertension patients.…”
Section: B Meta-analysis Of the Relationship Between Gender And Medication Adherence Of Hypertensive Patientsmentioning
confidence: 99%
“…The pooled odds ratio value is 1.14 with a 95% confidence interval of 0.91 -1.4. The assumption of most research studies that there is no relationship between gender and adherence to treatment for hypertension patients suggests that women and men have equal opportunities to adhere to hypertension treatment [18]). There is no difference between the level of compliance of women and men, especially by adjusting the level of education.…”
Section: B Meta-analysis Of the Relationship Between Gender And Medication Adherence Of Hypertensive Patientsmentioning
confidence: 99%
“…This validated questionnaire was used to assess patient's adherence level towards antihypertensive medication. The MMAS-8 has been demonstrated to have good concurrent and predictive validity and might function as a screening tool in outpatient settings as has been widely used in various other studies to measure medication adherence [9,15] . Hence, MMAS-8 was used in this study for its validity, quick and easy to complete.…”
Section: Data Collection Toolmentioning
confidence: 99%
“…Adherence to recommended antihypertensive medications is central to adequately control hypertension resulting in reduced cardiovascular morbidity and mortality and lower healthcare costs [6]. Socio-economic factors, healthcare system-related factors, context-dependent factors, physician/treatment-related factors, and patient-related factors were found to influence medication adherence [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that a signi cantly higher proportion of the group that was adherent named their drugs correctly and could also mention indication, dosage, timing, and duration of its use [6]. Furthermore, issues like not having somebody to help keep track of when to take medications, having the urge to take medication only when in discomfort and fear of side effects such as dizziness and headache have also been recorded as drivers to poor adherence to antihypertensive medications [7].…”
Section: Introductionmentioning
confidence: 99%